Elite cultures : anthropological perspectives - Shore, Cris, 1959-; Nugent, Stephen (Stephen L.) (A.S.A. monographs ;, 2002)
The anthropological study of elites has gained increasing prominence with the shift of the anthropological gaze toward issues of power, prestige and status in the societies of anthropologists themselves. However, our understanding of elites is often partial, obscured as it is by the theoretical weaknesses of Western models on the one hand and, on the other, by the difficulties in studying elites from the 'inside'. Drawing on a diverse, comparative ethnographic literature, this new volume examines the intimate spaces and cultural practices of those elites who occupy positions of power and authority across a variety of different settings. Using ethnographic case studies from a wide range of geographical areas, including Mexico, Peru, Amazonia, Indonesia, Sri Lanka, Europe, North America and Africa, the contributors explore the inner worlds of meaning and practice that define and sustain elite identities. They also provide insights into the cultural mechanisms that maintain elite status, and into the complex ways that elite groups relate to, and are embedded within, wider social and historical processes.; The book addresses a number of fundamental questions about the nature of elites and society such as; *How do elites in different societies maintain their position of domination? *How do elites reproduce themselves over time? *How do elites represent themselves? *How can we study elites anthropologically? *What implications does this study have for the discipline of anthropology? In exemplifying anthropology's contribution to the study of power, this book provides a welcome and timely addition to the literature as well as to current debates about the scope and direction of the discipline itself. Professor John Eade, University of Surrey, UK; Dr Sandra Evers Vrije Universiteit, The Netherlands; Dr.